THE ROLE OF HALAL TOURISM EAST JAVA IN PROMOTING CULTURAL EXCHANGE AND UNDERSTANDING - Yuli Yanti Wulansari; Candraningrat Candraningrat (Journal of Halal Research, Policy, and Industry, 2024)
This research aims to explore the role of halal tourism in East Java in promoting cultural exchange and intercultural understanding, as well as examining the influence of halal attributes, culture and halal tourism services on Muslim tourists' satisfaction and their revisit intention. Using quantitative methods with purposive random sampling, this research involved 200 respondents who were Muslim tourists visiting halal tourist destinations in East Java. Data was analyzed using SmartPLS to test the relationship between variables. The research results show that halal attributes have a significant positive influence on Muslim tourist satisfaction, with a p-value of 0.002 < 0.05. Local culture also has a significant positive effect on tourist satisfaction, with a p-value of 0.000 < 0.05. Halal tourism services, which include sharia-compliant accommodation and facilities, have a significant positive influence on tourist satisfaction, with a p-value of 0.004 < 0.05. Apart from that, high tourist satisfaction has been proven to increase the revisit intention to halal tourist destinations in East Java, with a p-value of 0.000 < 0.05. This research highlights the importance of developing halal attributes, promoting rich local culture, and improving tourism services in accordance with Islamic principles to increase tourist satisfaction and encourage repeat visits. These findings provide practical implications for tourism managers in East Java in their efforts to develop better and more sustainable halal tourism.